Effects of controlling grain growth mode on microstructures and properties of Cu foil - Junqing Han; Yuying Wu; Kai Zhao; Haoran Wang; Shushuai Liu; Xiangfa Liu (Journal of Materials Research and Technology, 2023)
By means of direct current electrodeposition, Cu foil with columnar grain growth and equiaxed grain growth with different average grain sizes were prepared. Electron backscatter diffraction (EBSD), X-ray diffraction (XRD), atomic force microscopy (AFM), and transmission electron microscope (TEM) were employed to elucidate the correlation between the microstructures and properties of Cu foil after a certain relaxation time under different grain growth methods. A remarkable preferential ratio of {220} orientation was exhibited in the columnar-grown copper. However, as the copper layer transitions to equiaxed grain growth, the superiority altered to {200} crystal orientation. This variability in grain orientation makes the copper layer profile of columnar crystal growth higher than that of equiaxed crystal formation. The twin boundary density in copper foil increases as the grain growth mode changes from columnar to equiaxed, and grain refinement is beneficial to increase the twin boundary density in the samples. And columnar crystal copper and equiaxed crystal copper show different twin characteristics. There are a few single-stage twin steps in columnar crystal copper and more multi-stage twin steps in equiaxed crystal copper. With an increase of twin boundary density, both the tensile strength and the ductility increase remarkably.